Rheumatoid nodule presenting as a buccal submucosal nodule: A rare presentation of a common disease. Issue 1 (12th September 2016) - Tay, Gerald Ci‐An; Sauer, David A.; Andersen, Peter E.
Abstract: Background: Rheumatoid nodules are a common manifestation of rheumatoid arthritis but buccal rheumatoid nodules are extremely rare. The purpose of this study was to report a rare case of a rheumatoid buccal nodule and a review of the literature. Methods and Results: This case is about a 79‐year‐old woman with rheumatoid arthritis who was taking methotrexate and hydroxychloroquine, presenting with an enlarging left buccal submucosal mass. An incisional biopsy showed features consistent with that of a rheumatoid nodule. The mass was managed expectantly and the patient was taken off methotrexate with a marked reduction in the size of the nodule. Conclusion: Submucosal rheumatoid nodules of the oral cavity are an extremely rare manifestation of rheumatoid arthritis but should be considered in the differential diagnosis in patients with a history of rheumatoid arthritis presenting with submucosal masses. © 2016 Wiley Periodicals, Head Neck 39 : E12–E14, 2017